Studi Penelitian Tindakan Kelas: Bagaimana Meningkatkan Pemahaman Matematis pada Siswa? - Rani Sugiarni; Ari Septian; Dadang Juandi; Siti Julaeha (Pendidikan Matematika STKIP Kusuma Negara, 2021)
Learning models that are not precise have an impact on low student understanding so that the student completeness score is still below 50%, so appropriate action is needed to improve the quality of learning so that students' understanding in learning mathematics increases. The purpose of this study was to determine the increase in mathematical understanding of students by using cooperative learning model type Snawbal throwing. This type of research is classroom action research through 3 cycles. The increase in learning outcomes is determined based on an increase in the average understanding of students, the attainment of absorption and learning completeness. Increment refers to the ratio between the value of cycle I, cycle II and cycle III. The results showed that the implementation of the snowball throwing type of cooperative learning model could improve students' mathematical understanding of set material. It can be seen from the students' average understanding of mathematics increased from 75 (cycle I) to 9 (cycle II), and 82 (cycle III). The increase also occurred in the attainment of absorption and learning completeness. The absorption capacity increased from 50% to 70% and 73%. The learning completeness has increased from 50% to 70% and 73%.